Perancangan Video Iklan Animasi 2D dengan Mengusung Karakter Cerita Rakyat Lokal dalam Rangka Mengenalkan Daerah Wisata Alam Baturraden Kabupaten Banyumas - Anjani, Viki; Kurniawan, Rendya Adi; Rachman, Anung (ArtComm : Jurnal Komunikasi dan Desain, 2023)
Tourism is an attraction for everyone to refresh the mind from the fatigue of daily activities or work. There are so many tours in Indonesia, one of which is natural tourism in the Baturraden area which is famous for its cool mountain tourism, but it is unfortunate because the promotion of tourism is still lacking. Therefore, the researcher aims to make or create a 2d animated video that carries the character of local folklore Baturraden to introduce and promote Baturraden natural tourism. The process of making this project takes data from journals, websites, google form surveys and other validated sources, then described in descriptive form using qualitative methods and Luther's MDLC (Multimedia Development Life Cycle) method. This research produces a 39-second video featuring a variety of illustrations and characters that can convey information about Baturraden's natural attractions. Based on the survey results shared through google form also stated the effectiveness of the video.